2006
DOI: 10.1083/jcb.200509122
|View full text |Cite
|
Sign up to set email alerts
|

A Maurer's cleft–associated protein is essential for expression of the major malaria virulence antigen on the surface of infected red blood cells

Abstract: The high mortality of Plasmodium falciparum malaria is the result of a parasite ligand, PfEMP1 (P. falciparum) erythrocyte membrane protein 1), on the surface of infected red blood cells (IRBCs), which adheres to the vascular endothelium and causes the sequestration of IRBCs in the microvasculature. PfEMP1 transport to the IRBC surface involves Maurer's clefts, which are parasite-derived membranous structures in the IRBC cytoplasm. Targeted gene disruption of a Maurer's cleft protein, SBP1 (skeleton-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
215
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(227 citation statements)
references
References 40 publications
(63 reference statements)
10
215
0
Order By: Relevance
“…Mutating residues 2-9, 10-14, 21-26, 27-31 and 32-35, respectively, did not affect trafficking of the chimeric protein to the Maurer's clefts ( Figure 5B). In comparison, introducing alanines at positions 16-20 (A [16][17][18][19][20] seemed to reduce the trafficking efficiency. Now, fluorescence was seen in a dotted pattern surrounding the parasite body and in the Maurer's clefts ( Figure 5B).…”
Section: Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutating residues 2-9, 10-14, 21-26, 27-31 and 32-35, respectively, did not affect trafficking of the chimeric protein to the Maurer's clefts ( Figure 5B). In comparison, introducing alanines at positions 16-20 (A [16][17][18][19][20] seemed to reduce the trafficking efficiency. Now, fluorescence was seen in a dotted pattern surrounding the parasite body and in the Maurer's clefts ( Figure 5B).…”
Section: Dmentioning
confidence: 99%
“…To test this hypothesis, we extended the alanine replacements creating A [10][11][12][13][14][15][16][17][18][19][20] and A [16][17][18][19][20][21][22][23][24][25][26] ( Figure 5A). A [10][11][12][13][14][15][16][17][18][19][20] exhibited the same partial phenotype as did A [16][17][18][19][20] ( Figure 5B). In comparison, substituting amino acids 16-26 by alanines ( Figure 5B) completely abrogated trafficking of the corresponding protein to the Maurer's clefts.…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeleton binding protein 1 (SBP1) and membrane-associated protein (MAHRP)1 localize to the Maurer's clefts (Blisnick et al, 2000;Spycher et al, 2003), parasite-induced vesicular structures in the host cell that are involved in the export of cytoadherence determinants to the RBC surface (Wickham et al, 2001;Knuepfer et al, 2005b). Interestingly, SBP1 has now been shown to be essential for export of PfEMP-1 to the RBC surface (Cooke et al, 2006). Thus, it seems that many ring stage-specific genes code for proteins that 1) show no homologies to proteins in other organisms and 2) are exported into the host cell and therefore may be involved in host cell modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Gene-deletion technology made it more possible to study the function of specific genes. First, knock out experiments eliminating the Maurer's clefts proteins MAHRP1 or SBP1 surprisingly revealed that PfEMP1 is not exported to the surface of the infected erythrocyte anymore (41,121,122). This finding was the first proof that Maurer's clefts have a function as an intermediate compartment in transport or sorting of proteins, at least for those destined for the erythrocyte membrane.…”
Section: Gene-deletion Studies Indicate Functions Of Maurer's Cleftsmentioning
confidence: 63%